The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement - Lawrence, John F. (Zootaxa, 2019)
An addendum to the revision of the Australian ciid fauna contains descriptions of 17 new species, information on recently described Australian species, addition of one described species new to the fauna, and corrections to the previous revision. Keys are provided to the Australian species of Cis, Notapterocis, Orthocis and Paratrichapus. The following new species are described: Cis apodemus, sp. nov., C. bicolorellus, sp. nov., C. brachytrichus, sp. nov., C. christmasensis, sp. nov.; C. densus, sp. nov., C. depressus, sp. nov., C. howensis, sp. nov., C. incomptus, sp. nov., C. latemarginatus, sp. nov., C. macilentus, sp. nov., C. occidentalis, sp. nov., C. prominens, sp. nov., C. pycnostictus, sp. nov., C. rhaibocerus, sp. nov., Notapterocis acutus, sp. nov., N. nesiotes, sp. nov., and Orthocis inordinatus, sp. nov.. Orthocis flavipennis (Pic) is recorded from Australia for the first time, and the Australian record of O. auriculariae Lawrence (Lawrence, 2016) is considered to be based on misidentified specimens of O. flavipennis. Notes are also included on the recently described Australian species by Souza-Gonçalves & Lopes-Andrade (2017): Scolytocis australimontensis and Xylographella frithae, and those described by Souza-Gonçalves et al. (2018): Paratrichapus australis, P. burwelli, P. christmasensis, P. metallonotum and P. peckorum.